Subprime Lending Foreclosures, Crime, and Neighborhood Disorganization: Beyond Internal Dynamics - Teasdale, Brent (American journal of criminal justice, 2012)
Research and theorizing about communities and crime has largely focused on internal neighborhood dynamics, to the neglect of factors external to the community that may be important processes in shaping community crime rates. We argue that subprime lending practices and the foreclosures that result may result in higher crime rates. We utilize data from the Summit County Lending Study, the Akron Police Department, and the 2000 U.S. Census to test the hypothesis that subprime lending foreclosures increase crime in urban neighborhoods. We find that subprime lending foreclosures have substantial impact on crime counts, net of controls. We conclude that additional research and theorizing about the role of external factors in the disorganization model is required.